Building muscle: nutrition to maximize bulk and strength adaptations to resistance exercise training - Tarnopolsky, M. A. (European Journal of Sport Science, 2008)
Several nutritional strategies can optimize muscle bulk and strength adaptations and enhance recovery from heavy training sessions. Adequate energy intake to meet the needs of training and carbohydrate intake sufficient to maintain glycogen stores (>7 g carbohydrate·kg-1·day-1 for women; >8 g carbohydrate·kg-1·day-1 for men) are important. Dietary protein intake for top sport athletes should include some foods with high biological value, with a maximum requirement of approximately 1.7 g·kg-1·day-1 being easily met with an energy sufficient diet. The early provision of carbohydrate (>1 g·kg-1) and protein (>10 g) early after an exercise session will enhance protein balance and optimize glycogen repletion. Creatine monohydrate supplementation over several days increases body mass through water retention and can increase high-intensity repetitive ergometer performance. Creatine supplementation can enhance total body and lean fat free mass gains during resistance exercise training; however, strength gains do not appear to be enhanced versus an optimal nutritional strategy (immediate post-exercise protein and carbohydrate). Some studies have suggested that -OH-methyl butyric acid (-HMB) can enhance gains made through resistance exercise training; however, it has not been compared "head to head" with optimal nutritional practices. Overall, the most effective way to increase strength and bulk is to perform sport-specific resistance exercise training with the provision of adequate energy, carbohydrate, and protein. Creatine monohydrate and -HMB supplementation may enhance the strength gains made through training by a small margin but the trade-off is likely to be greater bulk, which may be ergolytic for any athlete participating in a weight-supported activity.